Ivanhoe - Scott, Walter, Sir, 1771-1832.; Wilson, A. N., 1950- (New York : Penguin Books, 1986)
Relates the adventures of the Saxon knight Ivanhoe in 1194, the year of Richard the Lion-Hearted's return from the Third Crusade.
"First published 1819"--T.p. verso.
Includes bibliographical references.
Young Adult
Keywords: Knights and knighthood -- Fiction; Middle Ages -- Fiction; Historical fiction; Knights and knighthood -- Fiction; Middle Ages -- Fiction; Great Britain -- History -- Richard I, 1189-1199 -- Fiction; Great Britain -- History -- 1066-1485, Medieval period -- Fiction